2011
DOI: 10.1007/s00232-011-9348-8
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-β-Cyclodextrins Preferentially Remove Cholesterol from the Liquid Disordered Phase in Giant Unilamellar Vesicles

Abstract: Methyl-β-cyclodextrins (MβCDs) are molecules that are extensively used to remove and to load cholesterol (Chol) from artificial and natural membranes; however, the mechanism of Chol extraction by MβCD from pure lipids or from complex mixtures is not fully understood. One of the outstanding questions in this field is the capability of MβCD to remove Chol from lipid domains having different packing. Here, we investigated the specificity of MβCD to remove Chol from coexisting macrodomains with different lipid pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 39 publications
4
42
1
4
Order By: Relevance
“…For example, it increases membrane permeability to ions and thereby disrupts membrane potential 102 , and potentially is cytotoxic 103 . Moreover, this reagent appears to preferentially remove cholesterol from liquid-disordered (non-raft) domains in model membranes 104 , which can induce unexpected and inconsistent 21,67 effects on lipid packing in more complex membranes. Drugs targeting cholesterol synthesis (statins 105 and zaragozic acid 106 ) or cholesterol-modifying enzymes (e.g.…”
Section: Studying Lipid Raftsmentioning
confidence: 99%
“…For example, it increases membrane permeability to ions and thereby disrupts membrane potential 102 , and potentially is cytotoxic 103 . Moreover, this reagent appears to preferentially remove cholesterol from liquid-disordered (non-raft) domains in model membranes 104 , which can induce unexpected and inconsistent 21,67 effects on lipid packing in more complex membranes. Drugs targeting cholesterol synthesis (statins 105 and zaragozic acid 106 ) or cholesterol-modifying enzymes (e.g.…”
Section: Studying Lipid Raftsmentioning
confidence: 99%
“…Cyclodextrins are extensively used to remove cholesterol from artifi cial and natural membranes (see Ref. 42 ), and their effects on membrane properties have been explored using laurdan GP analysis. It has been shown that MbCD increases the fl uidity of biological membranes as assessed by a signifi cant reduction of laurdan GP ( 43 ).…”
Section: C-laurdan Gp Measurements In Guvsmentioning
confidence: 99%
“…It is known that for a phospholipid/Chol mixed membrane, cholesterol is preferentially removed by MβCD from a liquid disordered (L d )-phase749. In an L o phase, because of the close proximity of the phospholipids to the cholesterol molecules, the MβCD will have difficulty to reach the cholesterol molecules.…”
Section: Resultsmentioning
confidence: 99%